Gambaran Penerapan Sub Pokok Fungsi Dalam Fungsi Permintaan Dan Penawaran Pada Pembelajaran Matematika - Lusiani Lusiani; Andi Hendrawan; Kristian Cahyandi; Yogo Mardiantoro; Supriyanto Supriyanto (KOLONI, 2023)
In learning mathematics, there is an application of sub-functions that can be applied in economic mathematics, namely through the sub-discussion of the demand and supply functions. Methods in this study include observation and literature review. The research object is the cadets of the AMN Cilacap Commercial Shipping Management study program. Learning outcomes in the cognitive aspect were obtained using the observation method. The instrument used is the worksheet media. Observations are carried out relevant through indicators of active learning using worksheet media. The steps taken are described through mathematics lectures at KPN cadets. In general, it can be concluded that the sub-functions in the Demand Function in mathematics learning can be applied properly because the percentage is above 75%, namely 81.68%.  Keywords: demand function, supply function, sub function, mathematics